Microsatellite-assisted backcross selection in maize - Luciana Lasry Benchimol; Cláudio Lopes de Souza Jr.; Anete Pereira de Souza (Genetics and Molecular Biology, 2005)
A microsatellite marker (SSR) was chosen to simulate a target allele and three criteria (02, 04 and 06 markers per chromosome) were tested to evaluate the most efficient parameters for performing marker-assisted backcross (MAB) selection. We used 53 polymorphic SSRs to genotype 186 BC1 maize (Zea mays L.) plants produced by crossing the inbred maize lines L-08-05 (donor parent) and L-14-4B (recurrent parent). The second backcross (BC2) generation was produced with 180 plants and screened with markers which were not recovered from the first backcross (BC1) generation. A total of 480 plants were evaluated in the third backcross (BC3) generation from which 48 plants were selected for parental genotype recovery. Recurrent genotype recovery averages in three backcross generations were compatible with those expected in BC4 or BC5, indicating genetic gain due to the marker-assisted backcrossing. The target marker (polymorphic microsatellite PHI037) was efficiently transferred. Six markers per chromosome showed a high level of precision for parental estimates at different levels of maize genome saturation and donor alleles were not present in the selected recovered pure lines. Phenotypically, the plants chosen based on this criterion (06 markers per chromosome) were closer to the recurrent parent than any other selected by other criteria (02 or 04 markers per chromosome). This approach allowed the understanding that six microsatellites per chromosome is a more efficient parameter than 02 and 04 markers per chromosome for deriving a marker-assisted backcross (MAB) experiment in three backcross generations.